β-elemene enhances the radiosensitivity of gastric cancer cells by inhibiting Pak1 activation - Liu, Jun-Song (World journal of gastroenterology : WJG, 2015)
AIM:To explore the potential of β-elemene as a radiosensitizer for gastric cancer cells and the underlying mechanisms.METHODS:SGC7901,MKN45,MKN28,N87,and AGS human gastric cancer cell lines were used to screen for radioresistant gastric cancer cell lines. A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium(MTT) assay was used to determine the effects of β-elemene and IPA-3 on cell viability in MKN45 and SGC7901 gastric cancer cell lines. A clonogenic survival assay and annexin V-FITC/PI apoptosis detection assay were used to evaluate cellular radiosensitivity and radiation-induced cell death,respectively. A proteomic method,isobaric tags for relative and absolute quantitation(i TRAQ),was employed to screen the proteins regulated by β-elemene pretreatment prior to ionizing radiation(IR) in SGC7901 gastric cancer cell line. IPA-3 was used as a specific small molecule inhibitor of p21-activated protein kinase 1(Pak1) to target Pak1 signaling. Protein levels of PAK1IP1(p21-activated protein kinase-interacting protein 1),total Pak1(t-Pak1),phospho-Pak1(T423),phospho-ERK1/2( Thr202/Tyr204),and cleaved caspase-3(17 k Da) were assessed by western blotting.RESULTS:MKN45 and SGC7901 gastric cancer cell lines were relatively more resistant to IR. β-elemene pretreatment decreased clonogenic survival following IR in MKN45 and SGC7901 gastric cancer cell lines. Additionally,β-elemene pretreatment prior to IR increased radiation-induced cell death compared with IR alone in MKN45(10.4% ± 0.9% vs 34.8% ± 2.8%,P < 0.05) and SGC7901(11.6% ± 0.9% vs 46.7% ± 5.2%,P < 0.05) human gastric cancer cell lines,respectively,consistent with the level of cleaved caspase-3(17 k Da). Through i TRAQ analysis and western blot validation,we found that β-elemene upregulated PAK1IP1 and downregulated phospho-Pak1(T423) and phosphoERK1/2 in SGC7901 gastric cancer cells. IR increased the level of phospho-Pak1(T423). Pretreatment with β-elemene decreased radiation-induced Pak1 and ERK1/2 phosphorylation. Inhibition of Pak1 using IPA-3 decreased clonogenic survival following IR. In addition,IPA-3 increased radiation-induced cell death in MKN45(13.4% ± 0.3% vs 26.6% ± 1.0%,P < 0.05) and SGC7901(16.0% ± 0.6% vs 37.3% ± 1.7%,P < 0.05) gastric cancer cell lines,respectively,consistent with the level of cleaved caspase-3(17 k Da). Western blotting showed that IPA-3 decreased radiation-induced Pak1 and ERK1/2 phosphorylation.CONCLUSION:This is the first demonstration that β-elemene enhances radiosensitivity of gastric cancer cells,and that the mechanism involves inhibition of Pak1 signaling.